ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN PERTAMBANGAN BATUBARA - SAFITRI NURHIDAYATI (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2020)
ABSTRACT (Times New Roman 12 Point) The purpose of this thesis is to find out which coal mining companies listed on the Indonesia Stock Exchange that are predicted not to go bankrupt, are predicted to be in a gray area and are predicted to go bankrupt in the 2015-2017 period based on analysis using the Altman Z-Score method. The object of research is twenty-two coal mining companies. The data used in this study is a summary of the company's annual financial statements that are listed on the Indonesia Stock Exchange. The analysis technique used is the Altman Z-Score bankruptcy prediction model using the formula Z "= 6.56 X1 + 3.26 X2 + 6.72 X3 + 1.05 X4. With the evaluation criteria, Z-Score> 2.60 categorized as not bankrupt. Z-Score 1.1 - 2.60 is in the gray area. And the Z-Score <1.1 is categorized as bankrupt. Based on the results of the study showed that there were eleven companies categorized as not bankrupt namely PT Adaro Energy Tbk, PT Baramulti Sukses sarana Tbk, PT Golden Energy Mines Tbk, PT Garda Tujuh Buana Tbk, PT Harum Energy Tbk, PT Indo Tambangraya Megah Tbk, PT Resource Alam Indonesia Tbk, PT Mitrabara Adiperdana Tbk, PT Samindo Resources Tbk, PT Bukit Asam Tbk and PT Toba Bara Sejahtra Tbk. There are five companies in the gray area, namely PT Bayan Resources Tbk, PT Delta Dunia Makmur Tbk, PT Dian Swastatika Sentosa Tbk, PT Petrosea Tbk and PT Golden Eagle Energy Tbk. The company is predicted to bankrupt as many as six companies, namely PT Atlas Resources Tbk, PT Bara Jaya International Tbk, PT Borneo Lumbung Energy & Metal Tbk, PT Bumi Resources Tbk, PT Darma Henwa Tbk and PT SMR Utama Tbk.